Static and kinematic PPP using online services: a case study in Florida. Issue 2 (3rd July 2017) - Berber, Mike Mustafa; Ustun, Aydin; Yetkin, Mevlut
Abstract: In the not very distant past, many organisations began providing online GNSS data-processing services. Some of these services work on the differential positioning principle and some use precise point positioning. Moreover, these services provide the results for both static and kinematic modes – users only need to specify the mode of processing. In this study, both long-period static and short-period kinematic GNSS data are collected at seven NGS sites and processed using GAMIT, Track and online services. Time series from online processing services show a performance of a few decimetres for static data and sub-metre accuracy for 2 min of kinematic data.